DEVELOPMENT AND VALIDATION OF RELATED SUBSTANCES METHOD BY HPLC FOR ANALYSIS OF NAPROXEN IN NAPROXEN TABLET FORMULATIONS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A simple, selective, rapid, precise and isocratic reversed phase high-pressure liquid chromatography method has been developed and validated for estimation of related substances of Naproxen in pharmaceutical dosage form. It was performed on a YMC-ODS A Pack (5μ particles size) (250mm × 4.6mm) column using mobile phase containing Acetonitrile and 10 mM Ammonium acetate buffer pH 3.8 in ratio 550:450 v/v (pH 3.8 adjusted with acetic acid) at the flow rate 0.8 ml/min. Detection was performed at 254 nm and a sharp peak was obtained for Naproxen at a retention time at about 5.9 ± 0.01 min. Linear regression analysis data for the calibration plot showed there was a good linear relationship between response and concentration in the range 0.25-3μg/ml; the regression coefficient was 1.000. The detection (LOD) and quantification (LOQ) limits were 0.13 and 0.25μg/ml respectively. The method was validated for accuracy, precision, specificity, robustness, and detection and quantification limits, in accordance with ICH guidelines. Statistical analysis proved the method was precise, reproducible, selective, specific, and accurate for analysis of Naproxen and its impurities. The wide linearity range, sensitivity, accuracy, short retention time, and simple mobile phase showed that the method is suitable for routine quantification of impurities in Naproxen in pharmaceutical dosage forms with high precision and accuracy.